Implementasi Kurikulum Merdeka Pada Pembelajaran PAI Dalam Mengembangkan Program Penguatan Profil Pelajar Pancasila - Abdul Rahman; Sasmi Nelwati; Khadijah Khadijah (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The purpose of this field study is to investigate the implementation of the Independent Curriculum at the UNP Laboratory Development High School as well as how PAI learning is used in developing P5 at the UNP Laboratory Development High School. The study is conducted in the UNP Laboratory Development High School, using primary data from three PAI teachers and secondary data from the principal, curriculum deputy, and curriculum deputy. In this research, the author used observation, interviews, and documentation to collect data. They also used data analysis by means of data reduction, presentation, and conclusions. The results of research on the Implementation of the Independent Curriculum in PAI Learning in Developing P5 in UNP Laboratory Development High Schools include three topics, namely: first, planning, where in its implementation in schools, PAI teachers use teaching modules which include the Pancasila Profile of faith, devotion to God Almighty and with noble character, global diversity, mutual cooperation, critical reasoning and creativity. Second, Implementation, in its implementation the UNP Laboratory Development High School made a policy of 66% for subjects and 33% for P5 projects. third, the supporting factors in its implementation are complete facilities and infrastructure as well as the readiness of students and the inhibiting factor in implementing the independent curriculum is the application of different curricula at each local level at the UNP Laboratory Development High School making it difficult for teachers to design lessons.